Clarity of voter choices: neglected foundation for ideological congruence - Luana Russo; Mark N. Franklin; Stefanie Beyens (QOE-IJES, 2021)
Ideological congruence between voters and governments is desirable, the wisdom goes, because it implies enactment of policies close to those preferred by voters. Party polarization plays a paradoxical role here: more polarization reduces voter-government congruence if parties making up a government move away from the center-ground where most individual voters are located; yet increasing polarization permits those governments’ policies to become more distinct in the eyes of voters. This paper investigates how political system clarity helps to resolve this paradox. We examine the interplay of several sources of clarity and, in particular, of the joint role of party and voter polarization. We argue and find that, if polarization of survey respondents increases in step with party polarization, this provides clarity that can override party polarization’s negative effect on voter-government congruence. But other types of clarity also play important roles in accounting for the range of values that congruence takes on.